2014
DOI: 10.1155/2014/918103
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mechanical Properties and Constitutive Relation of an Aluminized Polymer Bonded Explosive at Low Temperatures

Abstract: Polymer bonded explosives (PBXs) are widely used as energetic fillings in various warheads, which maybe are utilized under extreme environments, such as low or high temperatures. In this paper, the dynamic response of an aluminized polymer bonded explosive was tested at a range of temperatures from −55°C to −2°C and a fixed loading strain rate (~700 s−1) with the split Hopkinson pressure bar (SHPB). The PBX tested is aluminized, which contains 76 wt% RDX, 20 wt% aluminum powder, and 4 wt% polymer binder, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…14 The dynamic response of an aluminized PBX over a temperature range of À55 C to À2 C and under a xed loading strain rate has been tested using the split Hopkinson pressure bar (SHPB). 15 Temperature strongly affects the mechanical response of PBXs. Few studies have investigated the properties of PBXs under dynamic and static loading over a wide temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…14 The dynamic response of an aluminized PBX over a temperature range of À55 C to À2 C and under a xed loading strain rate has been tested using the split Hopkinson pressure bar (SHPB). 15 Temperature strongly affects the mechanical response of PBXs. Few studies have investigated the properties of PBXs under dynamic and static loading over a wide temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…Cady et al [29] measured the compression of three extruded formulation binders (extruded Estane, plasticized Estane, and plasticized HTPB) as a function of temperature and strain rate, and found that the viscoelastic recovery rates of all three adhesives were dominant at [31,32] believed that the dependence of compressive strength on temperature and strain rate can be attributed to Young's modulus and fracture surface energy according to Griffith fracture criterion. Lin et al [33] found that the tested PBX is temperature-sensitive at low temperatures. This phenomenon is possible because of the polymer binder which is the most temperature-sensitive in the PBX compositions.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al. [33] found that the tested PBX is temperature‐sensitive at low temperatures. This phenomenon is possible because of the polymer binder which is the most temperature‐sensitive in the PBX compositions.…”
Section: Introductionmentioning
confidence: 99%
“…The development of constitutive models for polymer bonded explosives (PBXs), especially for load-deformation or stress-strain relationships, has received considerable attention in the energetic material field. The development of the constitutive equations usually starts with a series of experimental measurements with sophisticated equipment and techniques, followed by curve fitting of the experimental data based on a proposed model, and further testing and refinement by predicting mechanical properties [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%